Analisis Kinerja Bongkar Muat PT. Agung Raya - Putri, Aprilia Nurcantika; Marpaung, Edward; Ayutia, Yolla (Institut Transportasi dan Logistik Trisakti, 2025)
A good job is one where completion time is short and accurate. To support the progress and get the results of loading and unloading performance measurement, it is necessary to use the right method of working time measurement and workload calculation to provide accurate information on the optimal time and workload size. PT Agung Raya is a private company engaged in logistics services. This kind of research is quantitative. This study directly measured work time, namely 3 containers of stripping activities and 3 containers of release cargo activities. The time-motion study method aims to determine the standard time of each work element, the amount of productivity and non-productivity, and the optimal workload for stripping and release cargo activities. The result of the standard time for stripping activities is 82 minutes with 74% productivity and release cargo activities require 52.3 minutes to complete with 88% productivity. The results of the workload analysis for the stripping and release cargo activities, which are owned by the workforce, exceed 100%, so there are suggestions for additional labour.